The rhetoric on Reproductive Health Bill a case study of the Pastoral statement of Bishop Nereo P. Odchimar, DD - Petras, Shelly Monique P.
In the Philippines, the Reproductive Health Bill is so controversial as it is being opposed by most of the Roman Catholic Churches and Organizations, especially the leaders of the Catholic Bishop Conference of the Philippines. It was during the leadership of Bishop Nereo P Odchimar, DD (Bishop of Tandag, Surigao del Sur) from the years 2010-2011 wherein series of debates happened because of the introduction of the new version of the RH Bill. Bishop Odchimar is one of the Catholic leaders who strongly opposed the Reproductive Health Bill. Hence, it is important for the researcher to study the various communication tools, particularly the pastoral statements/letters presented by the CBCP President to analyze how he tried to persuade the audiences in supporting the campaign against RH Bill. Kenneth Burke's Theory in Dramatism, particularly the elements in the Dramatistic Pentad, the concepts in he Guilt-Redemption Cycle and the Ratio of Interplay of two or three elements were used in order to analyze the written five(5) pastoral statements made by Bishop Odchimar. After analyzing the pastoral statements, the researcher found out that the interplay of the pentads and other modes of persuasion, and the character of the anti-RH Bill campaign, are reflected in the kind of rhetoric that he has. Moreover, all the pastoral statements shared a common denominator, having a scene that focused on the Reproductive Health Bill and its social, moral, and medical implications. Bishop Odchimar, being one of the agents of change and as a religious leader, took part in the campaign against the RH Bill. The act of releasing the pastoral statements/letters is considered to be the means of informing the people about disadvantages of passing the RH Bill. His main purpose is to encourage all the citizens in the Philippines to debunk the RH Bill because it bastardizes the sanctity of life. He mainly utilized the medical researches and studies, constitutional by-laws, Biblical passages, and other rhetorical agencies or means to explain and justify his stand against the bill. Finally, limited studies in line with rhetorical analysis have been made here in the Philippines, thus, this study would provide additional information on rhetorical analysis have been made here in the Philippines, thus, this study would provide additional information on rhetorical criticism. Specifically, how Kenneth Burke's Dramatism theory can be useful in analyzing written documents, in this case the pastoral letters/statements of a religious leader